Office hysteroscopy – a novel diagnostic and therapeutic procedure - Baranowski, Włodzimierz; Doniec, Jacek; Bettocchi, Stefano (Menopause Review/Przegląd Menopauzalny, 2007)
The presented paper describes a novel hysteroscopic technique (mini-hysteroscopy) which can be performed without any analgesia or anaesthesia, so this procedure can be easily performed as an ambulatory office hysteroscopy. The first part of the review presents in detail the methodology of mini-hysteroscopy. New generation hysteroscopic telescopes measure only 3.5, 4 or 5 millimetres of outer diameter with operation channel and single flow sheath. Technical parameters of complete hysteroscopic set (special hysteroscopic pump, bipolar coagulation tools and surgical forceps, scissors, graspers, etc) are also presented in detail. Indications and potential contraindications as well as criteria of patients selection for office hysteroscopy are analysed. Major technical improvements like vaginoscopy instead of speculum use, gentle penetration of cervical canal without use of tenaculum, and surgical procedure inside the uterine cavity performed without touching the myometrial tissue, markedly diminish or even eliminate the pain for patients during this procedure. The effectiveness, feasibility and high rate of acceptability of mini-hysteroscopy by patients make this procedure the first line approach in diagnosis and treatment of abnormal uterine bleeding, uterine congenital and acquired abnormalities (adhesions, septum, small submucous myomas). Simultaneous use of laparoscopy and mini-hysteroscopy in sterility diagnosis and treatment is also presented. According to literature data and own experience of the authors, it can be stated that mini-hysterscopy is an effective, minimally invasive and very safe procedure for diagnosis and surgery of cervical canal and uterine cavity disorders. This review also demonstrates the advantages of mini-hysteroscopy over classical hysteroscopy or other procedures (D&C, hysterosalpingography) in the diagnosis and treatment of the pathologies mentioned above.